Memoirs on Pauperism and Other Writings Poverty, Public Welfare, and Inequality. - de Tocqueville, Alexis (University of Notre Dame Press, 2021)
The collection includes new translations of Tocqueville's works, including the first English translation of his Second Memoir, the original Memoir, a letter fragment considering pauperism in Normandy, and the ''Pauperism in America'' index to the Penitentiary Report. Alexis de Tocqueville was one of the most important thinkers of the nineteenth century, and his thought continues to influence contemporary political and social discourse. In Memoirs on Pauperism and Other Writings, Christine Dunn Henderson brings all of Tocqueville's writings on poverty together for the first time: a new translation of his original Memoir and the first English translation of his unfinished Second Memoir, as well as his letter considering pauperism in Normandy and the ''Pauperism in America'' appendix to his Penitentiary Report. By uniting these texts in a single volume, Henderson makes possible a deeper exploration of Tocqueville's thought as it pertains to questions of inequality and public assistance. As Henderson shows in her introduction to this collection, Tocqueville provides no easy blueprint for fixing these problems, which remain pressing today. Still, Tocqueville's writings speak eloquently about these issues, and his own unsuccessful struggle to find solutions remains both a spur to creative thinking today and a caution against attempting to find simplistic remedies. Memoirs on Pauperism and Other Writings allows us to study his sustained thought on pauperism, poverty assistance, governmental assistance programs, and social inequality in a new and deeper way. The insights in these works are important not only for what they tell us about Tocqueville but also for how they help us to think about contemporary social challenges. This collection will be essential not only to students and scholars of Tocqueville's thought, nineteenth-century France, and political economy, but also to all those interested in the issues of public assistance, associative life, voluntary associations, and charities. --